Lightweight gypsum brick / Mohd Iqmal Shah Ardiansah and Sallehan Ismail - Ardiansah, Mohd Iqmal Shah; Ismail, Sallehan (2023)
Construction industry is one of the industries that is thriving forward these days across the globe. In order to remain competitive and relevant in this field, various innovations and alterations are necessary to create improved patterns and formulas for an enhanced version of existing products. In this research study, it is about a study of how a lightweight brick reacts when its mixture which is sand, replaced with waste gypsum. The aim of this study is to minimise sand mining and reduce the disposal of waste gypsum, thereby ensuring the success of the replacement to be used in the industry.